Effect of Boswellia on Adjuvant Induced Rheumatoid Arthritis in Experimental Animals - Omnia Magdy Mohammed Hendawy; Della Grace Thomas Parambi (International Journal of Phytomedicine, 2018)
Arthritis is the most common systemic connective tissue disease. About 1% of the world's population is affected by RA; women are three times more often than men. Onset is most frequent between the ages of 40 and 50 years, but people of any age can be affected. Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disorder that may affect many tissues and organs, but principally attacks flexible joints. Although the cause of rheumatoid arthritis is unknown, autoimmunity plays an important role in both its chronicity and progression. The new trend of medical treatment of rheumatoid arthritis seeks new drugs with more efficacy and fewer side effects. Since tumor necrosis factor alpha (TNF-α) as well as other cytokines act as key players in the development of arthritis. Studies in the United States and Europe have shown that their use is less common in clinical settings, but has become increasingly more in recent years as scientific evidence about the effectiveness of herbal medicine has become more widely available. The present work investigates the effect of Boswellia on Adjuvant induced RA in Experimental Animals.